2016
DOI: 10.1371/journal.pone.0164105
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-20b (miR-20b) Promotes the Proliferation, Migration, Invasion, and Tumorigenicity in Esophageal Cancer Cells via the Regulation of Phosphatase and Tensin Homologue Expression

Abstract: Increasing evidence has indicated that many microRNAs participate in the development and progression of esophageal cancer and gene expression regulation. MicroRNA-20b (miR-20b) has been reported to be aberrantly expressed in various cancers, but its exact role in esophageal cancer cells remains unclear so far. Therefore, we detected the levels of miR-20b in esophageal tumor tissues and their adjacent normal tissues, and various esophageal cancer cell lines by qRT-PCR. We also explored the effects of miR-20b on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Although miR-20b may affect gene expression, we regarded TGFBR2 as the target of miR-20b in ES cells. Several studies have detected several target genes of miR-20b, including phosphatase and tensin homolog and matrix metalloproteinase 2 (19,20). Our cDNA array data indicated that TGFBR2 was the only miR-20b-target gene and was uniformly decreased in all five ES cell lines.…”
Section: Discussionmentioning
confidence: 68%
“…Although miR-20b may affect gene expression, we regarded TGFBR2 as the target of miR-20b in ES cells. Several studies have detected several target genes of miR-20b, including phosphatase and tensin homolog and matrix metalloproteinase 2 (19,20). Our cDNA array data indicated that TGFBR2 was the only miR-20b-target gene and was uniformly decreased in all five ES cell lines.…”
Section: Discussionmentioning
confidence: 68%
“…Increasing numbers of studies have indicated that miRNAs are involved in various biological processes, such as cell reproduction, differentiation, apoptosis, and metabolism, as well as tumorigenesis [17]. Recently, it has been revealed that altered expression of miRNA contributes to the invasion and metastasis of many cancers [4,6,18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been revealed that altered expression of miRNA contributes to the invasion and metastasis of many cancers [4,6,18]. Increasing numbers of studies have indicated that among numerous other miRNAs, miR-543 is also involved in the processes of initiation and maintenance of many kinds of cancers, including ESCC [17]. It has also been reported that miR-543 is down-regulated in breast cancer [19] and endometrial cancer [20] but functions as an oncogene in hepatocellular carcinoma [10,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations